2015
DOI: 10.3390/rs71215816
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Land Surface Albedo Changes in the Broader Mediterranean Area, Based on 12 Years of Satellite Observations

Abstract: Abstract:The Land Surface Albedo (LSA) was estimated in the broader Mediterranean area, on an 8-day basis, for the period 2001-2012. MODIS (Moderate Resolution Imaging Spectroradiometer) albedo product parameters, at 1 kmˆ1 km spatial resolution, were used. LSA changes during the above study period were also estimated, based on annual average values. Results revealed increasing LSA trends dominating in the Levant region and decreasing in NW Africa, of the order of 3.3% and´6.6%, respectively, while mixed signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The MODIS 16-day 1 km albedo products (MCD43B3, collection5) from 2001 to 2011 were used in this study. The product contains the black-sky albedo (BSA) and the white-sky albedo (WSA), which can be used to calculate the actual (blue-sky) albedo based on the fraction of diffuse skylight [49,50]. Considering the small difference and high correlation between BSA and WSA [44,[51][52][53], WSA was used as the index of albedo in this study.…”
Section: Surface Albedo Data Setmentioning
confidence: 99%
“…The MODIS 16-day 1 km albedo products (MCD43B3, collection5) from 2001 to 2011 were used in this study. The product contains the black-sky albedo (BSA) and the white-sky albedo (WSA), which can be used to calculate the actual (blue-sky) albedo based on the fraction of diffuse skylight [49,50]. Considering the small difference and high correlation between BSA and WSA [44,[51][52][53], WSA was used as the index of albedo in this study.…”
Section: Surface Albedo Data Setmentioning
confidence: 99%
“…The findings showed that the surface albedo trend in the Levant region increased by 3.3 percent and decreased by 6.6 percent in North Africa, while different signs were observed in Southern Europe. Also, the findings showed that changes in land surface cover, changes in precipitation, and the optical thickness of airwaves play an important role in surface albedo anomalies (Benas and Chrysoulakis, 2015). To analyze the albedo trend in the Tibetan Plateau, the albedo of the MODIS was compared with the default of the WRF model in the period from 2000 to 2009.…”
Section: Introductionmentioning
confidence: 99%